Innovation for Sustainable Business - Zdonek, Iwona; Szromek, Adam R. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We invite you to read the Special Issue on innovation for sustainable business. It is a collection of 7 articles published in a Special Issue of Sustainability MDPI in 2021-2022. Many of the articles in this reprint are related to leadership. In the context of sustainable development, issues such as dynamic capabilities, CSR, succession management and innovative projects were addressed. Sustainable innovation is also considered from other perspectives. One of them is the topic of introducing sustainable innovations to new ventures. In addition, drivers and impacts of eco-innovation were also examined. There was also research in the area of ​​live commerce, which includes the perspective of consumer behavior.